Profile of Students' Mathematical Spatial Reasoning Ability in Cube and Block Material in terms of Adversity Quotient in Class IX on SMP Negeri 1 Galesong Utara - Nurhikmah Nurhikmah; Abdul Rahman; Hamzah Upu (PT ARRUS Intelektual Indonesia, 2023)
This research is a descriptive qualitative research that aims to analyze the profile of students' mathematical spatial reasoning abilities in cubes and blocks in terms of adversity quotient in class IX at SMP Negeri 1 Galesong Utara. The research subjects consisted of three students who were selected based on their scores on the adversity response profile (ARP) questionnaire: one subject AQ climber type, one subject AQ camper type, and one subject AQ quitte type. Next, the researcher asked spatial reasoning ability test questions on cubes and blocks and conducted interviews with each subject. The spatial reasoning ability profile refers to three indicators: spatial visualization, mental rotation, and spatial orientation. The results showed that (1) AQ climber type students had good spatial visualization skills in turning block images into cube nets, AQ climber type students had good mental rotation skills in rotating cube images up to 180 degrees, AQ type climber climber students had good spatial orientation ability in determining an image that was not a beam view from the front. (2) Camper-type AQ students have good spatial visualization abilities in changing block shapes into cube nets; camper-type AQ students do not have good mental rotation skills in rotating cube shapes as far as 180 °, and camper-type AQ students have the ability to define an image that is not a frontal beam view. (3) Quitter-type AQ students did not have good spatial visualization skills in turning block images into cube nets, quitter-type AQ students did not have good mental rotation abilities in rotating cube shapes as far as 180 °, and quitter-type AQ students did not have good spatial orientation capabilities in determining images that were not a beam view from the front.